Factors Affecting Junior High School Students' 4C Skills: An Empirical Study - Putri, Dwi Anggraini Harita; Usmeldi, Usmeldi (Postgraduate, University of Mataram, 2023)
The purpose of this research is to find out factors that can affecting Junior High School Students' 4C Skills such as self-efficacy, learning motivation, liveliness, mathematical literacy, and scientific literacy can significantly influence students' 4C skills. This study is quantitative research using a survey method. In addition, the effect of each construct on the 4C skills is estimated through the Partial Least Square Structural Equation Model (PLS-SEM). The research results show that self-efficacy, scientific literacy, learning motivation and activeness have a significant effect on 4C skills. Mathematical literacy does not have a significant effect on 4C skills, but scientific literacy has a mediating effect on the relationship between mathematical literacy and 4C skills. Therefore, it is expected that students will further improve their skills in realizing the demands of globalization.